2016
DOI: 10.1016/j.jenvp.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Where to put your best foot forward: Psycho-physiological responses to walking in natural and urban environments

Abstract: Mood improved in natural and urban environments  Salivary cortisol reduced in natural and urban environments  Restorative experience was higher in natural environments  Greater cognitive benefits of natural environments were seen 30 min after leaving the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
245
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(286 citation statements)
references
References 44 publications
(66 reference statements)
12
245
1
11
Order By: Relevance
“…There is a large body of literature that suggests that green environments have a restorative effect [10,11] and that this effect can be seen when walking in green space in both healthy [4,6] and clinical [5,7] populations. Recent research has suggested that even a short exposure to a static green scene is associated with improved behavioral performance on a sustained attention task when compared to short exposure to an image of a built urban environment devoid of nature [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of literature that suggests that green environments have a restorative effect [10,11] and that this effect can be seen when walking in green space in both healthy [4,6] and clinical [5,7] populations. Recent research has suggested that even a short exposure to a static green scene is associated with improved behavioral performance on a sustained attention task when compared to short exposure to an image of a built urban environment devoid of nature [36].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, walking in nature has been shown to be beneficial for both well-being [3][4][5] and cognition [6,7]. The literature suggests that the difference between directed (top-down) attention, where an environment demands increased cognitive effort, such as a busy road crossing, and involuntary (bottom-up) attention, where features of an environment are interesting as opposed to demanding, may contribute the mechanism for the beneficial effect of nature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the evidence for changes in neuroendocrine measures such as cortisol secretion is inconsistent. Findings show that outside the occupational context, walks in natural settings lowered cortisol levels more than urban walks (Lee et al 2011;Park et al 2010), have had no effects in comparison to urban walks (Tyrväinen et al 2014), or have had positive effects similar to those of urban walks (Gidlow et al 2016).…”
Section: Relaxation Exercise and Park Walk As Recovery Activitiesmentioning
confidence: 84%
“…For example, a study in the United Kingdom used wearable sensors to demonstrate the effects of a short walk in a green space on brain activity that might be associated with enhanced relaxation and restoration (Aspinall et al 2015). It was also shown that walking in natural environments produces stronger short-term cognitive benefits than walking in the residential urban environment (Gidlow et al 2016a). Cortisol measures have demonstrated that gardening alleviated acute stress faster than reading (van den Berg and Custers 2011).…”
Section: Improved Relaxation and Restorationmentioning
confidence: 99%